Isolation of mucosa-associated microbiota dysbiosis in the ascending colon in hepatitis C virus post-sustained virologic response cirrhotic patients - Midori, Yohei; Nosaka, Takuto; Hiramatsu, Katsushi; Akazawa, Yu; Tanaka, Tomoko; Takahashi, Kazuto; Naito, Tatsushi; Matsuda, Hidetaka; Ohtani, Masahiro; Nakamoto, Yasunari (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Achieving sustained virologic response (SVR) in patients infected with hepatitis C virus (HCV) reduces all-cause mortality. However, the mechanisms and risk factors for liver fibrosis and portal hypertension post-SVR remain incompletely understood. In the gut-liver axis, mucosaassociated microbiota (MAM) substantially influence immune and metabolic functions, displaying spatial heterogeneity at the anatomical intestinal site. We analyzed MAM composition and function to isolate the locoregional MAM involved in chronic liver disease progression in HCV post-SVR patients.We collected MAM samples from three intestinal sites (terminal ileum, ascending colon, and sigmoid colon) via brushing during colonoscopy in 23 HCV post-SVR patients and 25 individuals without liver disease (controls). The 16S rRNA of bacterial DNA in specimens collected with a brush and in feces was sequenced. The molecular expression of intestinal tissues and hepatic tissues were evaluated by quantitative real-time PCR. Results: In the post-SVR group, the microbial β-diversity of MAM, especially in the ascending colon, differed from the control group and was associated with liver fibrosis progression. In PICRUSt analysis, MAM in the ascending colon in the liver cirrhosis (LC) group showed compromised functions associated with the intestinal barrier and bile acid production, and FGF19 expression was markedly decreased in the terminal ileum biopsy tissue in the LC group. At the genus level, six shortchain fatty acid (SCFA)-producing bacterial genera, Blautia, Alistipes, Roseburia, Agathobaculum, Dorea, and Pseudoflavonifractor were reduced in the ascending colon of post-SVR LC patients.In patients of HCV post-SVR, we identified the association between the degree of liver fibrosis and dysbiosis of mucosa-associated SCFA-producing bacterial genera that may be related to intestinal barrier and bile acid production in the ascending colon.